2020
DOI: 10.30605/25409190.188
|View full text |Cite
|
Sign up to set email alerts
|

EFL Students’ Experiences in a Flipped Reading Comprehension Classroom

Abstract: The aim of this research is to investigate EFL students’ experiences that appear in EFL students during the application of the flipped classroom learning model. The research was conducted by using a qualitative approach and descriptive method. The research participants were nine first-grade students at one of the public senior high school in Karawang. The participants were divided into three groups: three low-level students, three middle-level students, and three high-level students. To collect the data, resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…Ramadhanty, S., and Puspitaloka, N. (2020) [10] Focusing on the challenges of implementing ERT-based instructions to promote students' engagement during instructional practices.…”
Section: Quantitative Methods 67mentioning
confidence: 99%
See 3 more Smart Citations
“…Ramadhanty, S., and Puspitaloka, N. (2020) [10] Focusing on the challenges of implementing ERT-based instructions to promote students' engagement during instructional practices.…”
Section: Quantitative Methods 67mentioning
confidence: 99%
“…It is therefore possible to state that using the flipped classroom approach during distance education positively affects students' achievements and motivation. Similarly, Ramadhanty et al [10] investigated the experiences of EFL learners using the flipped classroom during the pandemic era. The students faced several challenges; however, the results showed that learners had a positive attitude toward the flipped classroom experience.…”
Section: Distance Education and Flipped Classroommentioning
confidence: 99%
See 2 more Smart Citations
“…It showed that motivation came from internal and external factors. Moreover, Ramadhanty & Puspitaloka (2020) on her study entitle EFL students' experiences in a flipped reading comprehension classroom showed that learning english with media made students had positive feeling because they can more enjoy and active during learning process. In addition, Lubis et al (2019), his study entitle students' experiences of learning English in Indonesia: some effective and ineffective ways.…”
Section: Introductionmentioning
confidence: 98%